Stab resistant analysis for body armour design features manufactured via fused deposition modeling process - Chong, See Ying (UTeM, 2018)
Stab resistant body armour is a type of protective equipment worn to prevent from sustaining severe injuries caused by the sharp weapons. Despite many efforts have been devoted to enhance the protection and manoeuvrability of the body armour, current protective solutions continue to present a number of issues which has shown to affect the work performance of the wearers. Yet the application of additive manufacturing (AM) technology has potentially presented as an alternative solution to produce light weight body armour that able to provide adequate protection and performance characteristics due to the nature of AM build process. This research therefore attempted to investigate the feasibility to manufacture five designs of imbricate scale armour features for stab resistant application via Fused Deposition Modeling (FDM) process in order to meet the requirement of the knife resistance (KR) level one of the current HOSDB stab-resistant body armour standard with impact energy of 24 Joules. To do this, knife blades were fabricated in accordance with the international standard and securely installed to the Instron CEAST 9340 Drop Impact Tower which used to impact test on the test specimens. The test specimens were manufactured via Stratasys Fortus 400mc machine using two of the basis FDM filament materials including ABS-M30 and PC-ABS for a light weight stab resistant body protective armour. Prior to the experimental stab test, a preliminary study was performed via ANSYS which is a finite element analysis software to analyse stab resistance performance of these materials. Then, stab experimental test was conducted on both of the materials measured thickness ranging from 4.0 mm to 6.0 mm to ensure a proper material selection for stab resistance. By using the selected material, stab test was further conducted on the specimens measured thickness ranging from 7.0 mm to 10.0 mm to determine a minimum thickness resulted with a knife penetration through the underside which did not exceed the maximum penetration permissibility of 7.0 mm, as defined within HOSDB KR1-E1. The minimum thickness was then used to develop a series of designs incorporated with different imbricate scale-like features and stab tested to analyse their stab-resistant performance. Finally, one of the design which offered the highest knife penetration resistance was selected. Result obtained in the finite element analysis demonstrated the total deformation distributed in most of the PC-ABS specimens was lower than ABS-M30. This was also demonstrated in the stab experimental test of PC-ABS specimens which showed less shattering cases and lower overall knife penetration depth in comparison with ABS-M30. By using PC-ABS, further stab test demonstrated a minimum thickness of 8.0 mm can be used for the development of FDM-manufactured body armour design features. Lastly, the design feature of D5 has shown to exhibit the highest resistance to the knife penetration due to the penetration depth of 3.02 mm occurred in it was the lowest compared to other design features.